2015
DOI: 10.1037/a0038543
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory power posing affects nonverbal presence and job interview performance.

Abstract: The authors tested whether engaging in expansive (vs. contractive) "power poses" before a stressful job interview--preparatory power posing--would enhance performance during the interview. Participants adopted high-power (i.e., expansive, open) poses or low-power (i.e., contractive, closed) poses, and then prepared and delivered a speech to 2 evaluators as part of a mock job interview. All interview speeches were videotaped and coded for overall performance and hireability and for 2 potential mediators: verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 69 publications
(111 reference statements)
3
118
2
3
Order By: Relevance
“…Their findings suggest that the impact of power posing may be quite limited, or at the least, subject to moderation by very specific conditions such as gender, awareness of the hypothesis of the experiment or the "cover story" variable, timing of the posture, and the experimenters' blindness to the experiment. In their rebuttal, Carney, Cuddy, and Yap (2015) discussed evidence of expansive posture and power posing research across 33 studies and suggested Ranehill et al's results are due to methodological differences. However, that summary did not include quantitative analyses across findings.…”
Section: Contribution To Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Their findings suggest that the impact of power posing may be quite limited, or at the least, subject to moderation by very specific conditions such as gender, awareness of the hypothesis of the experiment or the "cover story" variable, timing of the posture, and the experimenters' blindness to the experiment. In their rebuttal, Carney, Cuddy, and Yap (2015) discussed evidence of expansive posture and power posing research across 33 studies and suggested Ranehill et al's results are due to methodological differences. However, that summary did not include quantitative analyses across findings.…”
Section: Contribution To Literaturementioning
confidence: 99%
“…It has also been associated with several behavioral indicators such as puzzle solving persistence (Riskind & Gotay, 1982), job interview performance and nonverbal presence (Cuddy, Wilmuth, Yap, & Carney, 2015). Research has yet to examine, however, a specific link between expansive posture and problem-solving through thought confidence.…”
Section: Metacognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…It improves our strengths, skills, decision taking and perception [8]. The study in [9] describes how participants who were asked to stay in expansive body postures that express power prior to a job interview, significantly outperformed participants who did not use the power postures before the interview.…”
Section: Lecture: Super Hero Posturementioning
confidence: 99%